2020
DOI: 10.3389/fonc.2020.574679
|View full text |Cite
|
Sign up to set email alerts
|

Adult Diffuse Low-Grade Gliomas: 35-Year Experience at the Nancy France Neurooncology Unit

Abstract: Background: To report survival, spontaneous prognostic factors, and treatment efficacy in a French monocentric cohort of diffuse low-grade glioma (DLGG) patients over 35 years of follow-up.Methods: A monocentric retrospective study of 339 patients diagnosed with a new DLGG between 01/01/1982 and 01/01/2017 was created. Inclusion criteria were patient age ≥18 years at diagnosis and histological diagnosis of WHO grade II glioma (according to 1993(according to , 2007(according to , and 2016. The survival par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 52 publications
2
43
0
Order By: Relevance
“…The treatment of LGG is a comprehensive treatment based on maximum surgical resection, but progression of deterioration is still inevitable, and patients often have adverse outcomes such as multicentre recurrence and meningeal dissemination 10‐12 . SUMOylation, as a covalent modification, occurs mainly in lysine residues 13 and plays an important role in maintaining protein stability and stress response 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of LGG is a comprehensive treatment based on maximum surgical resection, but progression of deterioration is still inevitable, and patients often have adverse outcomes such as multicentre recurrence and meningeal dissemination 10‐12 . SUMOylation, as a covalent modification, occurs mainly in lysine residues 13 and plays an important role in maintaining protein stability and stress response 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, postoperative residual lesion infiltration has been linked to the degree of disconnection of WM pathways, e.g., by showing a deterioration of theory of mind (empathy) related to the degree of tumor involvement of the right frontoparietal connectivity (arcuate fasciculus and cingulum) [ 49 ], or lexical retrieval worsening related to postsurgical residual glioma volume within the left inferior longitudinal fasciculus [ 50 ]. Another argument pleading in favor of earlier treatment is to prevent malignant transformation, not only for oncological purposes, since the initial glioma volume is correlated to the risk of degeneration and to survival [ 51 ], but also for functional reasons. As previously mentioned, the potential of neural redistribution is less in rapid-growing lesions (variable t-), explaining the higher rate of neurological disorders in high-grade glioma [ 20 ].…”
Section: Clinical Implications Of the Model: Towards New Insights Into The Oncofunctional Balancementioning
confidence: 99%
“…The ultimate aim should be to use the good treatment(s) at the optimal moment(s) according not only to the tumor genetics but also other prognostic parameters and patient’s expectations over time. Remarkably, recent series showed that applying this concept led to OS over 16 to 17 years while preserving the QoL for over one decade ( 10 , 11 ).…”
Section: The Alterative Way Of Multimodal and Adaptive Individual Decision Making Aiming To Anticipate The Story Years In Advancementioning
confidence: 99%
“…Twenty years later, it is now admitted that (i) beyond seizures, LGG patients suffer from cognitive and behavioral deficits at diagnosis even in incidental cases (4) (ii) this tumor will inescapably transform in higher grades, explaining the use of "lower-grade glioma" (mixing II/III) expression (5) (iii) early surgery is a main therapeutic factor (significant correlation between extent of resection and OS) (6, 7) (iv) early radiotherapy, at least given alone, is not associated with decreased mortality (6,8). These changes resulted in a longer life expectancy now over 15 to 16 years (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%